Assessment of HIV Infection in HIV Patients Admitted to Pakistan Institute of Medical Sciences, Islamabad, Pakistan - Akmal Zubair; Muhammad Ali; Rizwan Munir; Md. Belal Hossain (AIDS Research and Treatment)
Conclusion: Drug users often share needles and syringes with other users, which significantly contributes to the outbreak of HIV in society. Unmarried men exhibit a higher prevalence of HIV compared to married men. Increasing public awareness and implementing robust government policies could help reduce the rate of HIV infections.